2010
DOI: 10.1177/070674371005501002
|View full text |Cite
|
Sign up to set email alerts
|

Life Course Perspectives on the Epidemiology of Depression

Abstract: I n the 1980s, David Barker and colleagues (see Barker 1,2 and Barker et al 3,4) used hospital records from Hertfordshire, England, to link LBW to cardiovascular and respiratory disease later in life. They posited that certain adverse conditions in the womb can set the fetus on a pathway to lifelong ill health, a theory which became known as the fetal programming hypothesis. This groundbreaking work was a keystone in the foundation of the burgeoning field of life course epidemiology, which seeks to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
89
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 170 publications
(245 reference statements)
2
89
1
3
Order By: Relevance
“…These findings build upon a previous study that noted an association between lower levels of self-rated health and future depression in a population-based cohort 32 and a study of older adults in which self-rated health was found to identify those most at risk of depression.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings build upon a previous study that noted an association between lower levels of self-rated health and future depression in a population-based cohort 32 and a study of older adults in which self-rated health was found to identify those most at risk of depression.…”
Section: Discussionmentioning
confidence: 77%
“…Compared with those rating their health as good to excellent, those rating their health as poor to fair had a twofold greater risk of MDS up to 5 years later. The association between self-rated health and future depressive status remained strong even after adjusting for age, sex, multimorbidity, and baseline depression status or severity.These findings build upon a previous study that noted an association between lower levels of self-rated health and future depression in a population-based cohort 32 and a study of older adults in which self-rated health was found to identify those most at risk of depression.33 Participants rating their health as good to excellent had a risk of future depression similar to that of the general primary care patient population, 4,48 Note: Flowchart of participants who were active in the cohort at each year after they withdrew or died, and the number of active participants that returned the survey questionnaire. a N = 761.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…19 Multiple studies suggest that exposure to psychosocial risk factors and adversities, both chronic and acute, throughout the life course may increase individuals' chances for developing depression. [20][21][22] However, existing literature suggests that mental health disorders have a fairly strong genetic component [23][24][25] , and individuals with a high genetic risk for depression are likely to develop episodes of the disorder even without experiencing notable environmental stress. 26 Longitudinal studies have identified some early risk factors as being predictive of later depression in general populations, including low socioeconomic status, family history of depression, family conflict, early depressive symptoms, conduct problems, substance use, delinquent behavior, and negative life events.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that 2-bromo-1-(thietan-3-yl) imidazole-4,5-dicarboxylic acid salts and diylidenehydrazidеs may have an antidepressant effect. Depression refers to socially significant diseases, which is due to their high prevalence [6]. The study of the antidepressant activity of known drugs [7] and the search for new sources of antidepressant drugs are continuing [8].…”
Section: Introductionmentioning
confidence: 99%